Karakteristik Organoleptik Cookies Berbahan Dasar Hotong (Setaria italica) dengan Perbandingan Margarin dan Kenari (Canarium indicum) - Pays, Victory J; Tetelepta, Gilian; Moniharapon, Erynola (Jurnal Agrosilvopasture-Tech, 2025)
The aim of this research was to determine the appropriate ratio of margarine and canarium to produce the best millet cookies based on organoleptic properties. This research used a Completely Randomized Design with five levels of substitution treatment for margarine and canarium (100%:0%, 75%:25%, 50%:50%, 25%:75%, 0%:100%). Cookies with a substitution of 0% margarine: 100% canarium were liked by the panelists in term of color, aftertaste, taste, texture and produced cookies with a light yellow color, a slight aftertaste, a slight canarium taste, a texture that did not crumble when pressed.